2020
DOI: 10.3390/app10041279
|View full text |Cite
|
Sign up to set email alerts
|

Courtyard Sound Field Characteristics by Bell Sounds in Han Chinese Buddhist Temples

Abstract: The acoustic environments of Han Chinese Buddhist temples have long played an important role in the development of Buddhism. This study explored the effects of layouts and spatial elements of Han Chinese Buddhist temples on courtyard sound fields. First, sound fields of three traditional Han Chinese courtyards were measured, and results were compared with sound field simulations to determine the appropriate acoustic and software parameter setting for ancient building materials in the context of sound field sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Other studies have shown that fabric sound absorbers and Buddha statues installed in the main hall have an obvious influences on the sound field of Buddhist temples [50]. An increase in the height of a temple courtyard wall increases sound reflection and, in turn, significantly increases the sound pressure level of each courtyard and making the sound fields more uniform [51].…”
Section: Sound Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have shown that fabric sound absorbers and Buddha statues installed in the main hall have an obvious influences on the sound field of Buddhist temples [50]. An increase in the height of a temple courtyard wall increases sound reflection and, in turn, significantly increases the sound pressure level of each courtyard and making the sound fields more uniform [51].…”
Section: Sound Fieldmentioning
confidence: 99%
“…By combining sound field measurements with acoustic simulations, scholars have analysed the effects of spatial elements and sound source characteristics in the main hall of the Buddhist temple and found that both fabric sound absorbers and the position of Buddha statues had a pronounced effects on the sound field [50]. Additionally, the influence of the courtyard scale and layout factors on the sound field of Buddhist temple courtyards has been analysed [51]. In terms of soundscape evaluation, there is a significant correlation between the acoustic environment evaluation and the sound level measured in temples [18].…”
Section: Soundscapes In Buddhist Templesmentioning
confidence: 99%
“…The acoustic parameters of each enclosed interface material in the sound field model primarily include the sound absorption and scattering coefficients. When setting the parameters, we referred to the results of our previous study regarding the sound fields of ancient traditional Chinese buildings (Table 1) [42][43]. Before starting the simulation, the parameters were set according to the characteristics of the Odeon software.…”
Section: Sound Field Simulation and Verificationmentioning
confidence: 99%
“…Previous research on the acoustic environments of different religious places, such as Taoist temples, Buddhist temples, churches, and mosques, has focused on analysing the impact of architectural components, envelope materials, and sound sources on the reverberation time (T 30 ), sound distribution, and other indices of religious space through in situ measurements and simulations. In Buddhist temples and churches, higher courtyard walls of the temple and ceilings of the church enhanced sound reflection and sound field uniformity [3][4][5]. For mosques, the recommended T 30 for satisfying the needs of all acoustic scenes was greater than 1.0 s [6].…”
Section: Introductionmentioning
confidence: 99%